Genome-wide association mapping of genotype-environment interactions affecting yield-related traits of spring wheat grown in three watering regimes - Said, Alaa A.; MacQueen, Alice H.; Shawky, Haitham; Reynolds, Matthew P.; Juenger, Thomas E.; El-Soda, Mohamed (Elsevier, 2022)
Genotype-environment interaction (GxE) has a great impact on wheat physiology, morphology and grain yield (GY). We evaluated an association mapping panel of spring wheat advanced lines for chlorophyll content, canopy temperature (CT), and yield-related traits under three different watering regimes in two consecutive growing seasons. Genome-wide association mapping identified 457 SNPs, with significant effects that varied with the watering regimes and growing seasons, of which 199 and 69 SNPs showed pleiotropic and conditionally neutral effects, respectively, on the measured traits. We mapped 61 SNPs with effects higher than 10% on all traits, showing antagonistic pleiotropic effects on CT, corresponding to 46 genes; some of these genes represent good candidates to control wheat response to water availability. Surprisingly, no significant SNPs were mapped in the semi-dwarfing genes, Rht-B1b or Rht-D1b. However, haplotype analysis of the SNPs located at the positions of both genes revealed significant interactions of GY with the watering regimes for Rht-B1b and with the growing season for Rht-D1b. We selected genotypes that outperformed two local check cultivars; some of them overlapped across the three watering regimes and could be used to create a multi-parent population to further unravel the genetic factors underlying yield component traits across drought stress. Our results demonstrate the importance of incorporating GxE in mapping models to better understand wheat response to different watering regimes and to select stable markers for selection.